Measurement of energy poverty in the Colombian Caribbean region: a comparative analysis - Bayona-Velásquez, Etna; Núñez-Alvarez, José Ricardo; Pirela-Ríos, Ana; Marín-Giraldo, Ever (International Journal of Electrical and Computer Engineering (IJECE), 2023)
This research work is directed to analyze the level of energy poverty and its consequences on the quality of life of the population of the Colombian Caribbean region, by doing a comparison of the results obtained in that area with data regarding the population of Bogotá, capital of Colombia, and of the rest of the country. The method of meeting absolute energy needs was used to determine the energy poverty index at households (EPH). Results obtained indicate that EPH exceeds 60% in urban areas, and 96% in rural zones, where it was also evidenced a clear link between energy poverty and school dropout.